Risk management in internationally diversified portfolio and its foreign exchange risk mitigation - Vasylchenko, Anna; Brůna, Karel, 1973-; Boháčik, Ján; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
The main focus the submitted thesis “Risk Management in Internationally Diversified Portfolio and Foreign Exchange Risk Mitigation” is to analyze and determine the optimal structure of internationally diversified portfolio based on nine stock market indices during a specific period of time. For the purposes of this work, a US investor who is rational and risk-averse will be considered during the analytical part. The question as to how the investor could develop their portfolio to achieve most favorable mean-variance relationship will be intended to answer. The first section of the thesis presents specific risk factors of wealth diversification over different countries. The second section is dedicated to the motivation and background. The third and fourth sections represent Markowitz and Sharpe frameworks. The fifth part focuses on the solver agent. The sixths part describes selected market characteristics as well as specifics of each individual index. The final seventh section provides the analysis of risk, return, correlation, and Sharpe ratio of each specific index as well as the correlation of exchange rates. Once, these factors were computed, the respective optimal domestic portfolios were obtained. The following section also exhibits the ultimate internationally diversified portfolio.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses